2012
DOI: 10.1016/j.mvr.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel and simple method for culturing pericytes from mouse brain

Abstract: Pericytes play critical roles in the development, maturation and remodeling of blood vessels, and in the central nervous system (CNS), evidence suggests that pericytes also regulate blood flow and form an integral part of the blood-brain barrier. The study of this important cell type has been hampered by the lack of any pericyte-specific marker and by the difficulty of culturing pericytes in adequate numbers to high purity. Here we present a novel yet simple approach to isolate and culture large numbers of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 49 publications
4
84
2
Order By: Relevance
“…Primary Cultures of Pericytes and Vascular Endothelial Cells-Brain pericytes were prepared from cerebral cortices obtained from female rats 3 weeks postnatally as described previously with modifications (19). The cerebral cortices were digested in a mixture of 1 mg/ml collagenase type 2 (Worthington) and 6.7 g/ml DNase (Sigma) in Dulbecco's modified Eagle's medium (DMEM) for 90 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Primary Cultures of Pericytes and Vascular Endothelial Cells-Brain pericytes were prepared from cerebral cortices obtained from female rats 3 weeks postnatally as described previously with modifications (19). The cerebral cortices were digested in a mixture of 1 mg/ml collagenase type 2 (Worthington) and 6.7 g/ml DNase (Sigma) in Dulbecco's modified Eagle's medium (DMEM) for 90 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, in this study, validation of pericyte identity was done by immunofluorescence for smooth muscle actin (SMA), which is obviously not a pericyte-specific marker. In fact, a recent study even showed that SMA is a negative marker for pericytes [39], with additional reference to another study that stated: ''few freshly isolated pericytes express this antigen, but with time in culture, almost 100% of cells express a-SMA'' [40].…”
Section: Pericytes As Vascular Stem Cellsmentioning
confidence: 99%
“…In humans, pericytes are easily isolated from various tissues, including the lung, using fluorescence-activated cell sorting with the gating strategy CD45-/CD31-/CD56-, CD146 high [10,11]. In mice, pericyte isolation and/or characterization has generally relied on culture methods using cells isolated from the heart [12], ear [13] and brain [14], or through the use of transgenic mice in which pericytes are labelled in the kidney [15], skeletal tissue [16], liver [17], lung [18,19,20] and brain [21]. Fluorescence-activated cell sorting is a rapid method and yields pure populations, which is not possible using culture methods alone.…”
Section: Pericytes: An Overviewmentioning
confidence: 99%